ANALISIS STRATEGI SOCIAL MEDIA MARKETING DALAM MEMPERTAHANKAN BRAND AWARENESS PADA DOTATO DONAT KAMPUNG (Studi Kasus pada Instagram Dotato) - Jihan Hanifah Sony; Cecep Safa’atul Barkah (POLITEKNIK LP3I JAKARTA, 2024)
Dotato Donat Kampung, a prominent MSME in the culinary sector, has effectively built substantial brand awareness among students in Jatinangor. However, it faces challenges in sustaining this awareness. This research aims to analyze the social media marketing strategies employed by Dotato Donat Kampung to maintain its brand presence. Utilizing a qualitative approach with a descriptive method, the research involved detailed interviews with both the owners. The effectiveness of the social media marketing strategies was evaluated using the TOWS method. The findings indicate that Dotato Donat Kampung's social media marketing is fairly successful in boosting brand awareness and product sales, although there are certain Instagram features that have not been fully utilized. The analysis highlights the need to optimize the use of Instagram ads and broadcast channels to sustain brand awareness and broaden audience reach. Dotato Donat Kampung, a prominent MSME in the culinary sector, has effectively built substantial brand awareness among students in Jatinangor. However, it faces challenges in sustaining this awareness. This research aims to analyze the social media marketing strategies employed by Dotato Donat Kampung to maintain its brand presence. Utilizing a qualitative approach with a descriptive method, the research involved detailed interviews with both the owners. The effectiveness of the social media marketing strategies was evaluated using the TOWS method. The findings indicate that Dotato Donat Kampung's social media marketing is fairly successful in boosting brand awareness and product sales, although there are certain Instagram features that have not been fully utilized. The analysis highlights the need to optimize the use of Instagram ads and broadcast channels to sustain brand awareness and broaden audience reach.